Relasi Makna Antar Kalimat pada Berita Sindonews.com - Rachel Setiawati; Irma Heriana; Selpi Misda; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Indonesian semantics is a branch of linguistics that studies the types of meaning contained in a paragraph or sentence regarding the system of symbols and signs. In semantics, it describes various kinds of studies including Meaning Relations in each sentence, while what is studied in this study is related to the meaning relations between sentences that exist in online news sources. The news that became a study was taken from one of the online news outlets, namely Sindonews, with various kinds and types of news such as news about education, sports, economics, politics and even news about life and motivation from foreigners. So, in this study taking one source of news about education, the data obtained was about the various meanings contained and this study used a descriptive qualitative approach with the addition of content analysis methods that made the data sources obtained relevant. And the studies used in this study relate to the meaning of synonyms, homonyms, polysemy and antonyms.